A case study of using cosmic ray muons to monitor supercritical CO2 migration in geological formations. (1st January 2017) - Zhong, Jinjin; Jiang, Xi
Highlights: Carbon storage monitoring using cosmic ray muons is investigated. The accuracy of the method in terms of its resolution is studied. The muon propagation process causes energy loss and results in attenuation. The muon scattering effect which may lower the spatial resolution is evaluated. The monitoring method may be more applicable and effective for shallow monitoring. Abstract: In carbon dioxide (CO2 ) geological storage, the monitoring of the injected CO2 migration in underground storage is essential to understanding storage process and ensuring storage safety. An effective monitoring system will be required for decades into the future during storage phase to indicate the location where the injected fluids have extended to. A novel radiographic probing technique using naturally occurring cosmic ray muon radiations was introduced in recent years as a promising continuous and cost-effective candidate method. This method utilizes the ability of different materials to attenuate muons as the detection property. The feasibility of this technique still needs to be investigated in terms of higher simulation accuracy, the intrinsic spatial resolution, and response sensitivity for storage with impurities. In this study, simulations are performed to understand the sensitivity of this method in responding to the presence of the injected fluids in saline aquifer formations. The energy spectrum of the cosmic ray muons for different zenith angles at sea level is sampled according to the modified Gaisser's formula. The muon propagation process has been simulated with high fidelity by detailed description of different materials involved in the deployed geological model. The muon attenuation along different paths carries information on the interior of a monitored region and the muon scattering effect may lower the accuracy to locate the fluids. The intrinsic spatial resolution of this method is thus analyzed and found to be at a scale of several meters. This method aims to provide the basis for understanding the injected fluids behavior. The simulations show that the method is feasible and the injected fluids in saline aquifers can be identified with a high sensitivity.